PENGARUH STRESSOR PEKERJAAN TERHADAP MUTU PELAYANANPERAWAT DI BANGSAL RAWAT INAP RSUD SUKOHARJO - Muhammad Alwi Andi; Elsye Maria Rosa (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2015)
Stressor of nurse work is an inability of nurse to face any condition or situation in work environment. Stressor of work consist of workload, physical environment, individual, group, and organization which is the source of stressor. The research identified the effect of work stressor on the quality of nurse care in inpatient wards of Sukoharjo Regional Public Hospital. The type of research is quantitative research with Cross-Sectional approach. The populations are all nurses who served in inpatient wards of Sukoharjo Regional Public Hospital. The samples are 81 nurses by using total sampling. There was no workload effect on the quality of nurse care (p 0,365; B -0,104). There was physical environment effect on the quality of nurse care (p 0,004; B 0,818). There was indiviual effect on the quality of nurse care (p 0,001; B 1,875). There was no group effect on the quality of nurse care (p 0,555; B 0,244). There was no organization effect on the quality of nurse care (p 0,640; B 0,184). The negative effect of stress in high level influenced the care to patient. The higher the perceived work stress would influence the quality of nurse care in inpatient wards of Sukoharjo Regional Public Hospital.